A ceRNA network-mediated over-expression of cuproptosis-related gene SLC31A1 correlates with poor prognosis and positive immune infiltration in breast cancer - Lian, Weibin; Yang, Peidong; Li, Liangqiang; Chen, Debo; Wang, Chuan (Frontiers in Medicine, 2023)
Introduction Solute carrier family 31 member 1(SLC31A1) has been reported as the copper importer, and was identified to be involved in the process of “cuproptosis”. However, the mechanism of SLC31A1 in breast cancer remains unclear. Methods We examined the expression of SLC31A1 mRNA in breast cancer tissues and cell lines using Real-time PCR. The data for this study were obtained from The Cancer Genome Atlas (TCGA) database and analyzed via R 3.6.3. TIMER, UALCAN, GEPIA2, STRING, Metascape, Kaplan–Meier Plotter, starBase and miRNet websites were used for a comprehensive analysis of SLC31A1. Results Our study suggested that SLC31A1 mRNA was over-expressed in breast tumor tissue and breast cancer cell lines, and which was closely related to poor relapse-free survival (RFS) and distant metastasis-free survival (DMFS). In addition, we constructed a co-expression network of SLC31A1. Functional enrichment analysis indicated that they were mainly involved in copper ion transport. Interestingly, SLC31A1 expression was positively associated with all m6A-related genes, especially with YTHDF3 (r = 0.479). Importantly, the LINC00511/miR-29c-3p/SLC31A1 axis was identified as the most potential pathway promoting breast cancer progress by affecting copper transport. Furthermore, the expression level of SLC31A1 in breast cancer was positively correlated with tumor immune cell infiltration, immune cell biomarkers and cancer-associated fibroblast (CAF). Conclusion Up-regulation of SLC31A1 expression and regulation of copper ion transport mediated by LINC00511-miR-29-3p axis is related to poor prognosis and positively correlated with tumor immune infiltration in breast cancer.